The Scientific and Historical Value of Annotations on Astronomical Photographic Plates. (February 2016) - Schechner, Sara J.; Sliski, David
The application of photography to astronomy was a critical step in the development of astrophysics at the end of the nineteenth century. Using custom-built photographic telescopes and objective prisms, astronomers took images of the sky on glass plates during a 100-year period from many observing stations around the globe. After each plate was developed, astronomers and their assistants studied and annotated the plates as they made astrometric, photometric, and spectroscopic measurements, counted galaxies, observed stellar variability, tracked meteors, and calculated the ephemerides of asteroids and comets. In this paper, the authors assess the importance of the plate annotations for future scientific, historical, and educational programmes. Unfortunately, many of these interesting annotations are now being erased when grime is removed from the plates before they are digitized to make the photometric data available for time-domain astrophysics. To see what professional astronomers and historians think about this situation, the authors conducted a survey. This paper captures the lively discussion on the pros and cons of the removal of plate markings, how best to document them if they must be cleaned off, and what to do with plates whose annotations are deemed too valuable to be erased. Three appendices (please visit Supplementary Material, available online) offer professional guidance on the best practices for handling and cleaning the plates, photographing any annotations, and rehousing them.